Memory effect in Fe-Ag granular multilayers - L F Kiss; J Balogh; L Bujdosó; D Kaptás (Materials Research Express, 2021)
Magnetic memory effect was measured in Fe-Ag granular multilayers by employing the so-called stop-and-wait protocol in order to reveal super-spin glass (SSG) behavior and explore the role of intra- and interlayer interactions which can influence the superparamagnetic (SPM) behavior of Fe particles separated by Ag layers. Calculations based on the relaxation of two-level systems are made to obtain the evolution of the magnetization of interaction-free SPM particles as a function of temperature and time for arbitrary annealing procedures, e.g., zero-field-cooled (ZFC) and field-cooled (FC) susceptibility (low-field magnetization) or temperature-cycling measurements. In samples with a single Fe layer of different nominal thicknesses, both the observed memory effect and the low-temperature deviation of the measured FC magnetization from the calculated interaction-free FC curve are attributed to the effect of dipolar interactions. Estimates on the anisotropy energy suggest the importance of the surface anisotropy of the Fe particles in the magnetic behavior.